Generations in Black and White: Photographs from the James Weldon Johnson Memorial Collection - Van Vechten, Carl; Byrd, Rudolph P (University of Georgia Press, 1993)
This portfolio of eighty-three photographs constitutes a stunning celebration of African American achievement in the twentieth century. Carl Van Vechten, a longtime patron of black writers and artists, took these photographs over the course of three decadesprimarily as gifts to his subjects, such luminaries as W. E. B. Du Bois, Langston Hughes, Bessie Smith, Billie Holiday, Joe Louis, James Baldwin, Richard Wright, Ruby Dee, Lena Horne, and James Earl Jones. The photographs Rudolph P. Byrd has selected for this volume come from the James Weldon Johnson Memorial Collection of Negro Arts and Letters, which Van Vechten established at Yale University. Byrd has arranged the images chronologically, according to the time at which each subject emerged as a vital presence in African American tradition. Complementing the photographs are a substantial introduction by Byrd, biographical sketches of each subject, and poems by the noted writer Michael S. Harper. The result is a volume of beauty and power, a record of black excellence that will engage and inform new generations.